Improving Performance of Hybrid Graphene–Perovskite Photodetector by a Scratch Channel. (18th April 2019) - Chen, Ziyu; Kang, Zhe; Rao, Chaoping; Cheng, Yongfa; Liu, Nishuang; Zhang, Zhi; Li, Luying; Gao, Yihua
Abstract: As a remarkable potential material for optoelectronics, perovskite has been widely studied in photodetectors. Here, a channel structure on graphene is introduced to achieve efficient separation of carriers in perovskites by suppressing the leakage current. The fabricated horizontal graphene/perovskite/graphene (GPG) structure detector with a graphene–perovskite hybrid channel and a secondary perovskite channel shows a good performance with a responsivity of 22 mA W −1, on/off switch ratio of 2.6 × 10 3, and detectivity of 3.55 × 10 9 Jones at a bias voltage of 2 V and an effective area of 3 × 5 mm 2 . The channel prepared by a simple probe drawing process forms a horizontal Schottky structure that is effective in generating photocurrent. It is proposed that minimizing the thickness of the perovskite without reducing the absorption rate and maintaining one channel are effective ways to further improve the performance of the GPG detector. The photoresponse characteristics of the devices under illumination of different wavelengths are measured, showing wide spectral response range and linear optical power response. Finally, a flexible GPG detector on polyethylene terephthalate substrate is fabricated. It almost retains the same performance and shows good reliability and bendability. Abstract : A scratch 22 µm wide channel introduced by simple probe suppresses the leakage current and separates the photogenerated carrier pair. The GPG detector shows low dark current and high photocurrent, thereby a high on/off switching ratio. This structure can also be deposited on polyethylene terephthalate to fabricate a flexible device.